Implementasi Csr Pt. Chandra Asri Dalam Pengelolaan Sampah Rumah Tangga Melalui Bank Sandi Di Kota Cilegon : ( Kelurahan Tegal Bunder, Kecamatan Purwakarta) - Revi Afriza Putri (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Increasing the volume of waste is still a crucial issue in various regions, considering that the dense activity of people outside the home makes it difficult to manage waste. Factors that often occur are people's habits and mindset regarding the existence of waste, namely that the product cannot be reused. For this reason, there is a need for waste activities or programs through Corporate Social Responsibility (CSR) within the community such as a waste bank (Bank Sandi) which is the formation of cooperation with stakeholders which aims to manage organic and inorganic waste, provide income to the community, form independence and community empowerment in processing waste. This research aims to find out the stages in implementing CSR, find out the supporting and inhibiting factors in implementing CSR and find out the obstacles in implementing CSR for the residents of Tegal Bunder Village. The method used is qualitative with a case study approach. The research results explain that the stages of CSR implementation are planning, implementation, evaluation and reporting. The supporting factors are company commitment and the inhibiting factors are technical issues, infrastructure for collection and sorting, changing behavior, and no continuous implementation (regulations already exist). And the obstacles in implementing CSR that occur in Tegal Bunder Subdistrict are time segregation, selling to collectors, no involvement of residents, and place. The Corporate Social Responsibility (CSR) program through Bank Sandi has been running well in accordance with the laws and regulations regarding the Company in the form of a commitment carried out by the company on an ongoing basis with the involvement of industry, universities, government and the community.